Progress and prospect of the time-varying gravity in earthquake prediction in the Chinese Mainland - Zhu, Yiqing; Yang, Xiong; Liu, Fang; Zhao, Yunfeng; Wei, Shouchun; Zhang, Guoqing (Frontiers in Earth Science, 2023)
This paper mainly introduces the application and progress of the time-varying gravity in seismic research in Chinese Mainland. Since the Xingtai earthquake in 1966, China has begun relative gravity monitoring, trying to explore the relationship between gravity changes and seismic activities. The gravity changes before and after the Haicheng MS7.3 earthquake in 1975 and the Tangshan MS7.8 earthquake in 1976 were observed. In 1981, a high-precision metal spring gravimeter was introduced to carry out high-precision relative gravity observation in the key earthquake monitoring areas in western Yunnan. The gravity anomaly changes near the epicenters of the Lijiang MS7.0 earthquakes in 1996 were observed. In 1998, high-precision absolute gravity survey was introduced to carry out the overall scale gravity field monitoring in Chinese mainland, and the large-scale gravity change information before Wenchuan MS8.0 and Yutian MS7.3 earthquakes in 2008 was obtained, and the effective prediction opinions were given. After the Wenchuan MS8.0 earthquake in 2008, the integration of the national network and the regional network accelerated, forming the whole gravity observation network in Chinese mainland, which made a relatively successful medium-term prediction for a series of earthquakes with MS6.0 or above (such as Lushan MS7.0, Menyuan MS6.4, Jiuzhaigou MS7.0, etc.) in recent years, and played an important role in the study of earthquake mechanism and earthquake prediction level in China. Finally, the existing problems in time-varying gravity monitoring in China are pointed out, and the prospect of earthquake research by using time-varying gravity monitoring data is put forward.